The Effect of Ajwa Dates Fruit Extract on Follicle Stimulating Hormone (FSH), Graafian Follicle and Endometrial Thickness in Female Rats Exposed to Arsenic - Herdhika Ayu Retno Kusumasari (Journal of Global Pharma Technology, 2020)
Background: Arsenic exposure in humans can disrupt the reproductive system and reproductive organs in women, which can cause interference hormonal and fertility disorders. The pathogenesis of arsenic causes oxidative damage to the organs and reproductive system due to an imbalance between Reactive Oxygen Species (ROS) and antioxidants in the body. Ajwa dates contain powerful antioxidants that act as scavenger ROS as well as inhibit lipid peroxidase which stop reactions associated with oxidative stress. Objective: This study aims to determine the effect of Ajwa date extract on Follicle Stimulating Hormone (FSH) levels, Graafian follicle and endometrial thickness in female rats exposed to Arsenic Trioxide (As2O3) for 30 days. Methods : Experimental laboratory with 5 treatment groups, negative control group (without arsenic exposure), positive control (3 mg/kg BW arsenic), T1 (arsenic 3 mg/kg BW + date extract 2ml / kg BW), T2 (arsenic 3 mg / kg BW + date extract 4ml / kg BW), and T3 (arsenic 3 mg / kg BW + date extract 8ml / kg body weight). Results: Arsenic exposure significantly reduced FSH levels, Graafian follicle count and endometrial thickness. Conclusion: The administration of Ajwa date extract could significantly provide antioxidant protection in the treatment group with an increase in FSH levels, Graafian follicle count and endometrial thickness.